Après le boom : la laborieuse mise en œuvre de nouvelles régulations dans le secteur minier guinéen - Johannes Knierzinger (EchoGéo)
Since 2003, after a long period of liberalization, more than a dozen African countries have adopted new mining codes which distinguish themselves markedly from their liberal predecessors. Drawing on fieldwork in Guinea, the article retraces the different stages of the implementation process of such a “progressive” mining code, including its modification in 2013 due to the pressure of the mining industry, the adoption of application texts and the adaption of mining contracts, and the introduction of new practises and their supervision in and around the mines.